Correction: Template-free single pot synthesis of SnS2@Cu2O/reduced graphene oxide (rGO) nanoflowers for high performance supercapacitors. (25th July 2018) - Hatui, Goutam; Nayak, Ganesh Chandra; Udayabhanu, G.; Mishra, Yogendra Kumar; Pathak, Devendra Deo
Abstract : Correction for 'Template-free single pot synthesis of SnS2 @Cu2 O/reduced graphene oxide (rGO) nanoflowers for high performance supercapacitors' by Goutam Hatui et al., New J. Chem., 2017, 41, 2702–2716.